13(2-x)=7(x+8)

Simple and best practice solution for 13(2-x)=7(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(2-x)=7(x+8) equation:


Simplifying
13(2 + -1x) = 7(x + 8)
(2 * 13 + -1x * 13) = 7(x + 8)
(26 + -13x) = 7(x + 8)

Reorder the terms:
26 + -13x = 7(8 + x)
26 + -13x = (8 * 7 + x * 7)
26 + -13x = (56 + 7x)

Solving
26 + -13x = 56 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
26 + -13x + -7x = 56 + 7x + -7x

Combine like terms: -13x + -7x = -20x
26 + -20x = 56 + 7x + -7x

Combine like terms: 7x + -7x = 0
26 + -20x = 56 + 0
26 + -20x = 56

Add '-26' to each side of the equation.
26 + -26 + -20x = 56 + -26

Combine like terms: 26 + -26 = 0
0 + -20x = 56 + -26
-20x = 56 + -26

Combine like terms: 56 + -26 = 30
-20x = 30

Divide each side by '-20'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 | | 50-8x-4=18 | | 50-8x-5=18 | | 50-8x-6=18 | | 50-8x-12=18 | | 50-8x-11=18 | | 50-8x-13=18 | | 50-8x-14=18 | | 50-8x-14=15 | | 50-8x-14=19 | | 50-8x-17=19 | | 100-8x-17=19 | | 100-8x-16=19 | | 100-8x-15=19 | | 100-8x-15=22 | | 100-8x-15=23 | | 100-8x-7=13 | | 3x+15y=-21 | | 8(x-1)+6=22 | | 100x-80=800-10x | | 100x-20=200-10x | | y(4x-8)=10+x | | 100x+10=110-10x | | 100x+10=110-110x |

Equations solver categories